Top Universities or Top Higher Education Systems? - Millot, Benoit (International Higher Education, 2014)
In reaction to the focus of international university rankings on a tiny cluster of “world class universities”, attempts are being made to rank national higher education systems. This paper compares the results of the U21 system ranking with those of major university rankings, reviews the reasons for their similarities. It argues that system rankings are critical and suggests how to enhance their usefulness